Board of directors' gender diversity and intellectual capital efficiency: the role of international authorisation - Wasiu Abiodun Sanyaolu; Anthony Abiodun Eniola; Kenzhin Zhaxat; Kanbibi Nursapina; T.K. Kuangaliyeva; Jimoh Odunayo (Cogent Business & Management, 2022)
Despite the roles of intellectual capital (IC) as a competitive strategy for firm continued survival, its nexus with board gender diversity (BGD) has sparsely been investigated. The aim of this study is to analyse the effect of BGD on intellectual capital efficiency (ICF) of the listed deposit money banks (DMBs) in Nigeria. Using a panel data set of 11 banks from 2011 to 2020, we found that BGD has no significant negative effect on ICF with and without the moderating effect of international authorisation. Our finding indicates the need for the management to increase women representation and its quality on the board of directors. The study emphasizes the relevance of BGD on intellectual capital performance with significant implication for academic and practioners. We contribute to literature by examining the effect of BGD on ICF of listed DMBs in Nigeria.
Keywords: 650; Board gender diversity; international authorization and intellectual capital efficiency